General ((k,p),ψ)-Hilfer fractional integrals - Bouharket Benaissa; Huseyin Budak (Miskolc Mathematical Notes)
The main motivation of this study is to establish a general version of the Riemann-Liouville fractional integrals with two exponential parameters kp((k,p),ψ)k(k,p),ψ((k,p),ψ)